Analysis of Economic Growth in Indonesia Using the Error Correction Model - Hardi, Bima (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This research was conducted to look at the influence of foreign debt, savings, domestic loans and total factors of production on economic growth in Indonesia in the long term and short term using the error correction model (ECM) method. The results of the simultaneous test (F-test) of all independent variables have an influence on the dependent variable in the short term and long term. Foreign debt (X1) partially in the short term has no effect on economic growth in Indonesia and in the long term it does. Savings (X2) partially in the short term have no effect on economic growth in Indonesia and in the long term they do. Domestic loans (X3) partially in the short term and in the long term have no effect on economic growth in Indonesia. Total production factors (X4) partially in the short term and long term have a negative effect on economic growth in Indonesia.